Measuring energy and environmental efficiency interactions towards CO2 emissions reduction without slowing economic growth in central and western Europe. (1st February 2021) - Zhang, Jijian; Patwary, Ataul Karim; Sun, Huaping; Raza, Muhammad; Taghizadeh-Hesary, Farhad; Iram, Robina
Abstract: Given the economic growth and energy consumption patterns, most countries are striving to solve the problems of CO2  emissions reduction to achieve sustainable development. This paper employs an improved DEA model to measure energy and environmental efficiency for some selected countries in central and western Europe. In addition, the DEA window evaluation technique is applied to measure cross-sectional efficiency using two inputs (energy consumption, labor force), a desirable output (gross domestic product), and an undesirable output (CO2 emission) for the period from 2010 to 2014. The study finds that the UK ranks the highest position in term of energy and environmental efficiency. This shows that the UK has more effective policies regarding energy efficiency, consumption, production, import and energy intensity measures for sustainable economic growth as well as environmental protection. Ireland is the second-best country after the United Kingdom. The efficiency scores of the two countries are 0.99 and 0.89 respectively. On the empirical outcomes, this study suggests effective reforms in energy sector for countries with less energy efficiency that are still facing the problem of environmental degradation. Highlights: There is an urgent need to balance sustainable development and economic growth. DEA window technique was applied to measure cross-sectional efficiency. Ireland is second best country after UK with energy and environmental efficiency. The market-centric structure would be more useful and advantageous for the society. We provide recommendations about emission reduction with moderate economic growth.